A mathematical model of vertically transmitted vector diseases - Antonella Lupica; Annunziata Palumbo (Atti della Accademia Peloritana dei Pericolanti : Classe di Scienze Fisiche, Matematiche e Naturali, 2018)

(untitled)
A mathematical model of vector-borne infectious diseases is presented, which takes into account the local interactions between reservoirs and vectors, as well as the transmission from vectors to dilution hosts. In the model, vectors possess the ability to keep the virus within their own population through vertical transmission. The existence and the stability of disease free and endemic equilibria, together with the existence of backward bifurcation, are discussed.